Elevated Contribution of Low Nucleic Acid Prokaryotes and Viral Lysis to the Prokaryotic Community Along the Nutrient Gradient From an Estuary to Open Ocean Transect - Hu, Chen; Chen, Xiaowei; Yu, Liuqian; Xu, Dapeng; Jiao, Nianzhi (Frontiers in Microbiology, 2020)
Prokaryotes represent the largest living biomass reservoir in aquatic environments and play a crucial role in the global ocean. However, the factors that shape the abundance and potential growth rate of the ecologically distinct prokaryotic subgroups (i.e., high nucleic acid (HNA) and low nucleic acid (LNA) cells) along varying trophic conditions in the ocean remain poorly understood. This study conducted a series of modified dilution experiments to investigate how the abundance and potential growth rate of HNA and LNA prokaryotes and their regulating factors (i.e., protozoan grazing and viral lysis) change along a cross-shore nutrient gradient in the northern South China Sea. The results showed that the abundance of both HNA and LNA cells was significantly positively correlated with the abundance of heterotrophic nanoflagellates and viruses, whereas only HNA abundance exhibited a significant positive correlation with nutrient level. With a decreasing nutrient concentration, the potential growth rate of the HNA subgroup declined significantly, while that of the LNA subgroup was significantly enhanced, leading to an elevated relative potential growth rate of the LNA to the HNA subgroup under decreasing nutrient levels. Furthermore, our data revealed different regulatory roles of protozoan grazing and viral lysis on the HNA and LNA subgroups, with HNA suffering higher mortality pressure from grazing than from lysis in contrast to LNA, which experienced equivalent pressures. As the nutrient levels declined, the relative contribution of lysis to the mortality of the HNA subgroup increased significantly, in contrast to the insignificant change in that of the LNA subgroup. Our results indicated the elevated role of LNA cells in the prokaryotic community and the enhanced viral lysis pressure on the total prokaryotes under oligotrophic conditions, implying that virus-mediated mortality will shunt more carbon and energy flow within the microbial loop in the future ocean, in which oligotrophication will be strengthened due to continuous global warming.